Comparative diversity of aquatic plants in three Central European regions - Svitok, Marek; Zelnik, Igor; Bubíková, Kateřina; Germ, Mateja; Gaberščik, Alenka; Kochjarová, Judita; Oťaheľová, Helena; Paľove-Balang, Peter; Hrivnák, Richard (Frontiers in Plant Science, 2025)
Freshwaters are among the most threatened ecosystems globally, with biodiversity declining at far greater rates than the biodiversity of the most affected terrestrial ecosystems. There is an urgent need for accurate information on spatial patterns of freshwater biodiversity, a first step in effective conservation planning and management of these ecosystems. We explored patterns of aquatic macrophyte diversity in four waterbody types, rivers, streams, ponds and ditches, across three Central European regions. By analyzing local (α), among-site (β) and regional (γ) diversity, we assessed the roles of these ecosystems as biodiversity hotspots, particularly for red-listed species. Sampling 220 sites across Slovakia and Slovenia, we recorded 113 macrophyte taxa (31% of which were red-listed), with ponds and ditches consistently supporting higher α and γ diversity than running waters. β diversity was primarily driven by species turnover, with ponds displaying high heterogeneity linked to environmental variability. Our findings highlight the conservation value of artificial habitats like ditches and ponds, harbouring significant macrophyte diversity, including unique and threatened species. These results underscore the need to prioritize small waterbodies in biodiversity conservation strategies within agricultural landscapes.